(untitled) (Annals of Medical Research, 2026)
Aim: In recent years, a significant increase has been observed in the prevalence of allergic diseases during childhood. This study aims to determine the prevalence of asthma, allergic rhinitis, and atopic dermatitis among children aged 6–7 living in the city center of Malatya, as well as to analyze potential environmental and familial risk factors associated with these conditions. Materials and Methods: The study was conducted between December 2023 and January 2024 in primary schools located in central Malatya, using the International Study of Asthma and Allergies in Childhood (ISAAC) questionnaire protocol. A total of 431 children were included. Participants were evaluated based on demographic characteristics, environmental exposures, family history, and symptoms related to asthma, allergic rhinitis, and atopic dermatitis. The collected data were analyzed statistically. Results: Lifetime wheezing was reported in 20% of the children, while 18.6% reported wheezing within the past 12 months. The prevalence of physician-diagnosed asthma was 4.2%. Allergic rhinitis symptoms were reported in 32.7% of the children throughout their lifetime and in 29.9% during the last year, while the rate of physician-diagnosed allergic rhinitis was 6.7%. The lifetime prevalence of atopic dermatitis was 8.8%, and the physician-diagnosed rate was 2.6%. Family history of asthma, allergic rhinitis, atopic dermatitis, and premature birth were identified as significant risk factors (p<0.05). No statistically significant association was found with gender, exposure to tobacco smoke, pet ownership, mode of delivery, parental consanguinity, or the presence of mold in the home. Conclusion: These findings confirm that allergic diseases represent a significant public health burden among children in Malatya. The results specifically highlight family history and perinatal factors as major determinants of disease prevalence in this population.